An extension of the Euler Laplace transform inversion algorithm with applications in option pricing - Petrella, G. (Operations research letters, 2004)
We show that the Euler algorithm for Laplace transform inversion can be extended to functions defined on the entire real line, if they have specific decay features. Our objective is to apply the method to option pricing problems, specifically when inverting Laplace transforms of the option price in the logarithm of the strike.